Character, Responsibility, and Well-Being: Influences on Mental Health and Constructive Behavior Patterns - Danilo Garcia (Frontiers Research Topics, 2016)
Character can be defined as self-aware knowledge that helps the individual to set goals, values and ethical principles (Cloninger, 2004). This meta-cognitive dimension of human personality involves 'Theory of Mind', and is positively related to measures of well-being, mental health, and constructive behavior patterns. Research from at least three different fields, cultural (Shweder, Much, Mahapatra & Park, 1997), personality (Cloninger, 2004), and social psychology (Abele & Wojcizke, 2007) suggest that character can be organized along three broad principles: agency, which is related to the autonomy and the fulfillment and enhancement of the self; communion, which is related to engagement in the protection and relations to others such as families, companies or nations; and spirituality, which is related to the human ability to transcend the self and find and interconnection with all life and appreciation of the whole world around us (Haidt, 2006; Cloninger, 2013). Using the Temperament and Character Inventory (Cloninger, Svrakic & Przybeck, 1993) researchers have found that agentic (i.e., Self-directedness) and communal (i.e., Cooperativeness) values are associated to high levels of happiness, psychological well-being, and less violent behavior. Moreover, low Self-directedness and Cooperativeness is recurrent among individuals with all types of mental health problems, such as, depression, schizophrenia, anxiety disorder, autism spectrum disorders, attention deficit/hyperactivity disorder and et cetera. Spirituality, in coherence with agency and communion, guides the individual to seek self-realization in harmony with others and nature in the changing world (Cloninger, 2013). Seeing character as self-awareness of the self in three dimensions has also been associated to human responsibility and empowerment. This Research Topic will focus on all article types that put forward findings regarding: •Character as a protective factor against mental illness •Character's association to conduct disorders and violent behavior •Character as a promoter of happiness, life satisfaction, and well-being •The etiology of character •Longitudinal studies on character •Agency, communion, and spirituality as broad dimensions for the conceptualization of positive measures of mental health •Innovative methods to measure or conceptualize character •Non-linear effects of character on mental health •Character as a measure/conceptualization of responsibility •Character in school and work place settings •Character in relation to empowerment.